Responsibility of the Captain in Transporting Goods at Sea - Dimas Wibisono (Jurnal IPTEK, 2021)
In the provisions of Article 137 Paragraph (1) and (2) Law no. 17/2008 both the Grosss Tonnage 35 and motor boats Motor boats are less than Gross Tonnage 35 as well as for boats traditionally less than the Gross Tonnage 105, I insist on the point states: The captain is the leader on the ship who owns law enforcement authority and are responsible for safety, security and order of ships, and cargo goods obligation. In another provision it is also stated that the master is the leader of the ship, who every certain event must take a stand and act in accordance with skill, precision and wisdom,as required to carry out their duties (Article 342 paragraph (1)KUHD). As the leader of the ship, the master must be responsible all his actions against the ship and its cargo in all events that happens in the sea. From that the legislators gave a burden responsibility to the master as regulated in Article 342 paragraph (2) KUHD, that is, if the action is committed in that position is intentional or negligent, which causes damage to other people.The breadth obligations given by law, in the implementationtransportation in terms of the responsibility of the Ship Leader / Master to safety, security and order of ships and sailors in essence boils down to the interests of the cargo as the agreed object which is the obligation of the carrier. The obligation that arises from its existence an agreement as intended gives birth to responsibilities implicitly it is the responsibility of the transportation company. The formulation of these provisions includes the extent of the obligations given by Constitution. If you listen to the process of organizing deep transportation regarding the responsibility of the Ship Leader / Master for safety, security and order of ships and sailors basically boils down to in the interest of cargo as the agreed object is the obligation of the carrier.